AN AUTOMATIC AND METHODOLOGICAL APPROACH FOR ACCESSIBLE WEB APPLICATIONS - Moreno, Lourdes; Castro, Elena; Martinez, Paloma (Journal of Information and Organizational Sciences, 2007)
Semantic Web approaches try to get the interoperability and communication among technologies and organizations. Nevertheless, sometimes it is forgotten that the Web must be useful for every user, consequently it is necessary to include tools and techniques doing Semantic Web be accessible. Accessibility and usability are two usually joined concepts widely used in web application development, however their meaning are different. Usability means the way to make easy the use but accessibility is referred to the access possibility. For the first one, there are many well proved approaches in real cases. However, accessibility field requires a deeper research that will make feasible the access to disable people and also the access to novel non-disable people due to the cost to automate and maintain accessible applications. In this paper, we propose one architecture to achieve the accessibility in web-environments dealing with the WAI accessibility standard and the Universal Design paradigm. This architecture tries to control the accessibility in web applications development life-cycle following a methodology starting from a semantic conceptual model and leans on description languages and controlled vocabularies.